INNOVATIVE MEANS FOR UNLOADING STEM FEED FROM TRENCH STORAGE - RUTKEVYCH, VOLODYMIR; KUSHNIR, V.; OSTAPCHUK, O. (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The issue of increasing the efficiency of the process and technical means for unloading stem fodder from trench storage facilities is considered. The need to create modern, high-tech and competitive equipment for livestock enterprises, appropriate size series of farms with different technologies for keeping animals, focusing on the use of prefabricated structures and equipment in block-modular design. Because the existing equipment does not meet the zootechnical requirements for stalk feeders (the density of feed in storage is disturbed to a depth of 2-2.5 m, which leads to refermentation of feed and reduced nutritional value). The main directions of development of stalk feeders are presented, which are aimed at reducing the loss of feed nutrients when unloading them from widely used trench storage facilities, which is an important problem of feed production. Their constructive and technological executions and the most optimum variant of execution are presented. The necessity of equipping these technical means with intelligent (adaptive) drives of working bodies in order to reduce the power of executive hydraulic motors is indicated. The creation of innovative means for unloading stem fodder from trench storage will increase the level of mechanization of loading and unloading operations, the quality of the technological operation of separating feed from the feed monolith and reduce the cost of agricultural products. Recommendations for maintaining the aerobic stability of feed in the feed monolith and increase the efficiency of the means for unloading stem feed from trench storage are given.
Keywords: innovative technologies; stem fodder; loader; trench; drive; working bodies; power; efficiency; productivity